1980
DOI: 10.1051/jphyscol:1980850
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Expanded Liquid Rubidium by Neutron Diffraction

Abstract: The static structure factor, S(Q), of liquid rubidium has been studied by neutron diffraction for temperatures up to 2000 K and pressures up to 139 bar near saturation conditions, corresponding to an expansion of the liquid from 1.46 to 0.54 gcm-3. The characteristic changes of the scattering behaviour and of the microscopic structure approaching the M-NM transition region are discussed. A comparison of these results with simple hard sphere model calculations is given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
60
3

Year Published

1989
1989
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(71 citation statements)
references
References 0 publications
8
60
3
Order By: Relevance
“…It is quite evident that our observation is different from those of the previous observations [10,11] in which microscopic structural variation is essentially similar to that of rare-gas liquids. The shortening of r 1 is seemingly consistent with the appearance of diatomic molecules as suggested by the inelastic neutron scattering measurements [20].…”
Section: Article In Presscontrasting
confidence: 56%
See 3 more Smart Citations
“…It is quite evident that our observation is different from those of the previous observations [10,11] in which microscopic structural variation is essentially similar to that of rare-gas liquids. The shortening of r 1 is seemingly consistent with the appearance of diatomic molecules as suggested by the inelastic neutron scattering measurements [20].…”
Section: Article In Presscontrasting
confidence: 56%
“…Several diffraction measurements have been carried out for expanded fluid alkali metals. Franz et al [10] measured the neutron diffraction for fluid Rb up to the critical region. They reported that the local structure of expanded fluid Rb changes in the way that is similar to that of simple liquids; the coordination number decreases linearly while the nearest-neighbor distance is almost unchanged or slightly increased.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Special experimental high-temperature high-pressure techniques have been developed in order to deal with the problem of containing highly corrosive metals in uncontaminated form in these extreme thermodynamic conditions. In particular, a quite complex cell has been designed for neutron diffraction studies in these systems (Freyland, Hensel & Glaser, 1979) and successfully employed for measurements of the static structure factor in liquid Cs (To= 1924K, Pc=92.5x 0108-7673/92/040508-08506.00 10 SPa) and Rb (Tc=2090K, Pc=140x10 SPa) (Franz, Freyland, Glaser, Hensel & Schneider, 1980;Freyland, Hensel & Glaser, 1984;Winter & Bodensteiner, 1988;Winter, Hensel, Bodensteiner & Glaser, 1987). The manufacture of such a cell opens the possibility of studying the microscopic properties of many fluids in critical conditions, even though the neutron scattering investigation turns out to be complex.…”
Section: Introductionmentioning
confidence: 99%